Pengembangan profesionalisme guru SMP Negeri 1 Duampanua Kabupaten Pinrang melalui pelatihan penulisan karya tulis ilmiah - Andi Agustang; Sirajuddin Saleh; Rusman Rasyid; Andi Tenri Pada Agustang (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) partner is the Technical Implementation Unit (UPT) of Junior High School of 1 Duampanua. The problem is: (1) the low motivation of teachers in preparing scientific papers (KTI). (2) The lack of knowledge and ability of teachers in preparing scientific papers (KTI) as an activity to develop professionalism of teachers. The external target is the Junior High School of 1 Duampanua teacher. The methods used are: lectures, demonstrations, discussions, questions and answers, observation and direct practice. The results achieved are (1) partners have motivation in compiling scientific papers (KTI). (2) The partners have the knowledge and ability to compile scientific papers (KTI) as teacher professional development activities.